The Influence of Culture on Occupational Therapy Practice in Jordan - Somaya H. Malkawi; Nisrin S. Alqatarneh; Elaine K. Fehringer (Hindawi-Wiley, 2020)
Background. Occupational therapy's origins draw from Western culture, values, and beliefs which may impact the application of traditional occupational therapy practice in non-Western cultures. Purpose. This study explored how occupational therapists in Jordan facilitate occupational therapy practice within Islamic Eastern culture. Method. A phenomenological approach was used in this study. Semistructured interviews were conducted with eleven occupational therapists that work in Jordan and have at least two years of experience. Data were analyzed using thematic analysis methods. Results. Three central themes emerged: impact of Jordanian culture and Islamic beliefs about independence and disability on occupational therapy practice, the therapists' notions of ideal occupational therapy practice vs. daily reality, and challenges posed by workspace and the availability of equipment. Conclusion. This study highlights the growing need to translate and expand the core values of occupational therapy to align with cultures in non-Western countries and cultures.